Pituitary Actions of EGF on Gonadotropins, Growth Hormone, Prolactin and Somatolactins in Grass Carp - Qiongyao Hu; Qinbo Qin; Shaohua Xu; Lingling Zhou; Chuanhui Xia; Xuetao Shi; Huiying Zhang; Jingyi Jia; Cheng Ye; Zhan Yin; Guangfu Hu (Biology, 2020)
In mammals, epidermal growth factor (EGF) plays a vital role in both pituitary physiology and pathology. However, the functional role of EGF in the regulation of pituitary hormones has rarely reported in teleost. In our study, using primary cultured grass carp pituitary cells as an in vitro model, we examined the effects of EGF on pituitary hormone secretion and gene expression as well as the post-receptor signaling mechanisms involved. Firstly, we found that EGF significantly reduced luteinizing hormone (LHβ) mRNA expression via ErbB1 coupled to ERK1/2 pathway, but had no effect on LH release in grass carp pituitary cells. Secondly, the results showed that EGF was effective in up-regulating mRNA expression of growth hormone (GH), somatolactin α (SLα) and somatolactin β (SLβ) via ErbB1 and ErbB2 and subsequently coupled to MEK1/2/ERK1/2 and PI3K/Akt/mTOR pathways, respectively. However, EGF was not effective in GH release in pituitary cells. Thirdly, we found that EGF strongly induced pituitary prolactin (PRL) release and mRNA expression, which was mediated by ErbB1 and subsequent stimulation of MEK1/2/ERK1/2 and PI3K/Akt/mTOR pathways. Interestingly, subsequent study further found that neurokinin B (NKB) significantly suppressed EGF-induced PRL mRNA expression, which was mediated by neurokinin receptor (NK2R) and coupled to AC/cAMP/PKA signal pathway. These results suggested that EGF could differently regulate the pituitary hormones expression in grass carp pituitary cells.